Biochemical characterization of serpins in the malaria vector, Anopheles gambiae - Gulley, Melissa M. (Kansas State University, 2013)
To date malaria is the most important tropical disease, which is caused by Plasmodium sp. and vectored by anopheline mosquitoes. The mosquito’s immune system is one of the limiting factors of malaria transmission. Immune reactions, such as the prophenoloxidase (PPO) pathway result in the melanization of pathogens, and are effective at limiting parasite numbers. Novel strategies for malaria control aim to exploit the immune system to interrupt parasite transmission by boosting the immune responses in the mosquito vector. Serpins play a crucial role in regulating protease cascades involved in immunity of arthropods. In Anopheles gambiae, the major malaria vector in Sub-Saharan Africa, 18 SRPN genes encoding 23 distinct proteins have been identified. So far, two are identified as active inhibitors, and both affect parasite survival. This research aims to identify additional inhibitory serpins in An. gambiae and elucidate their potential function. Identification of such serpins will enhance our understanding of the immune system of this important vector species and may identify immunoregulators to be used in malaria control. SRPN7, 9, and 18 were tested for their ability to inhibit commercial proteases in vitro. Recombinant SRPN18 had no inhibitory activity, while SRPN7 and 9 inhibited several serine proteases. SRPN7, 9 and 18 were tested against two recombinant An. gambiae clip serine proteases (CLIPBs) that are required for activation of phenoloxidase and thus regulate melanization. Only SRPN9 strongly inhibited CLIPB9 in vitro, suggesting that this serpin is a potential negative regulator of melanization. This hypothesis is further supported by the finding that SRPN9 can inhibit PO activity in insect hemolymph, ex vivo. Taken together, this research identifies SRPN18 as the first non-inhibitory serpin described in mosquitoes. Additionally, this study describes the larval-specific SRPN7 as a functional inhibitor. Future studies on these proteins will elucidate their precise physiological functions. Finally, this thesis provides strong evidence that SRPN9 is a negative regulator of melanization in An. gambiae and may therefore affect pathogen survival within this important vector species.
Keywords: Insect Innate Immunity; Serine Protease Inhibitor (serpin); Serine Protease; Biochemistry (0487); Biology (0306); Molecular Biology (0307)